Pengaruh Self-Regulation terhadap Motivasi Lulus Tepat Waktu pada Mahasiswa Tata Rias dan Kecantikan Universitas Negeri Padang - Theresia Anggiana Sitanggang; Prima Minerva (Universitas Palangka Raya, 2026)
This study addresses the issue of Cosmetology and Beauty students failing to complete their studies on schedule. It investigates the influence of self-regulation on the motivation to graduate on time, employing a quantitative, causal-associative method. A sample of 90 respondents was selected from the total population. Data analysis involved reliability, validity, and chi-square tests. The findings reveal that 47% of students demonstrated a moderate level of self-regulation, while 41% showed a moderate level of motivation to graduate on time. The chi-square test confirmed the influence of self-regulation on the motivation to graduate on time. Consequently, the study concludes that self-regulation is a crucial factor in the motivation to graduate on schedule. Students are therefore advised to enhance their self-regulation skills—such as goal setting, time management, monitoring academic progress, and self-control—throughout their studies. Additionally, the study program is encouraged to provide support through academic coaching, guidance, and mentoring initiatives designed to strengthen students' self-regulation and thereby boost their motivation to graduate on time.